EDUCATION IN THE CONTEXT OF “GENDER” AND THE ESSENCE OF TEACHING THE CONCEPT OF CHARACTERISTIC (Academicia Globe: Inderscience Research, 2023)
Gender issues in education article of the development of national traditions, in derogation of the rights of women in the national legislation on the elimination of all forms of generally recognized international norms, it added to the norms of international documents on gender equality of the republic of uzbekistan the practical implementation of the recommendations identified in the monitoring and analysis will be completed.